2009
DOI: 10.1038/sj.bjc.6605311
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of HIF-1 and drug penetrance to oxaliplatin resistance in hypoxic colorectal cancer cells

Abstract: BACKGROUND: Hypoxia is as an indicator of poor treatment outcome. Consistently, hypoxic HCT116 colorectal cancer cells are resistant to oxaliplatin, although the mechanistic basis is unclear. This study sought to investigate the relative contribution of HIF-1 (hypoxia-inducible factor-1)-mediated gene expression and drug penetrance to oxaliplatin resistance using three-dimensional spheroids. METHODS: Hypoxia-inducible factor-1a function was suppressed by the stable expression of a dominant-negative form in HCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 20 publications
1
40
1
2
Order By: Relevance
“…Many of these HIF-1 inducible genes such as VEGF, Glut-1, MDR, and Bcl-2 directly or indirectly mediate chemoresistance 19 .Therefore, in a wide range of different tumor types, e.g. hepatocellular carcinoma, neuroblastoma, and lung cancer, inhibition of HIF-1α resensitizes cells to drug treatment in hypoxia and is then a valid target to reverse hypoxia-induced drug resistance 8,9,15,19,21,25,[27][28][29][30]56 . HIF-1α accumulation has been associated with shorter survival in patients with early stage cervical, breast, ovarian, endometrial, oropharyngeal squamous cell carcinoma, and oligodendroglioma.…”
Section: Hif-1 and Chemoresistancementioning
confidence: 99%
See 1 more Smart Citation
“…Many of these HIF-1 inducible genes such as VEGF, Glut-1, MDR, and Bcl-2 directly or indirectly mediate chemoresistance 19 .Therefore, in a wide range of different tumor types, e.g. hepatocellular carcinoma, neuroblastoma, and lung cancer, inhibition of HIF-1α resensitizes cells to drug treatment in hypoxia and is then a valid target to reverse hypoxia-induced drug resistance 8,9,15,19,21,25,[27][28][29][30]56 . HIF-1α accumulation has been associated with shorter survival in patients with early stage cervical, breast, ovarian, endometrial, oropharyngeal squamous cell carcinoma, and oligodendroglioma.…”
Section: Hif-1 and Chemoresistancementioning
confidence: 99%
“…In this context, the most studied transcription factor is hypoxia-inducible factor-1 (HIF-1). HIF-1 is an important factor in the adaptation of cells to hypoxic environments, and significantly contributes to the aggressiveness and chemoresistance of number of different tumours 5,[7][8][9]15,19,21,[25][26][27][28][29][30] . However, these changes can be independent of HIF-1 (ref.…”
Section: Introduction -Hypoxia-induced Chemoresistancementioning
confidence: 99%
“…We have previously shown that hypoxic regions of HCT116 spheroids were less prone to apoptosis induced by the conventional cytotoxic agent oxaliplatin when compared with normoxic regions (24). Expression of a dominant negative (DN) HIF-1 prevents upregulation of the glucose transporter GLUT-1 in hypoxic regions of HCT116 spheroids (24).…”
Section: Cells Were More Sensitive Tomentioning
confidence: 99%
“…We have previously shown that hypoxic regions of HCT116 spheroids were less prone to apoptosis induced by the conventional cytotoxic agent oxaliplatin when compared with normoxic regions (24). Expression of a dominant negative (DN) HIF-1 prevents upregulation of the glucose transporter GLUT-1 in hypoxic regions of HCT116 spheroids (24). GLUT-1 and HIF1-α colocalized in these spheroids ( Figure 3A).The same 3D culture model was used here to investigate fur- ther the hypoxic sensitization to ABT-737, where CC3 was used to report apoptosis and GLUT-1 was used to report hypoxia.…”
Section: Cells Were More Sensitive Tomentioning
confidence: 99%
“…Hypoxia in tumors is important clinically, because expression of Hif1α (5,6) and Hif2α (7) proteins is correlated with poorer prognosis. Hif1α expression is also associated with resistance to fluorouracil (5-FU) (8) and oxaliplatin (9).…”
mentioning
confidence: 99%